2013 IEEE International Conference on Communications (ICC) 2013
DOI: 10.1109/icc.2013.6655206
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency analysis of secondary networks in cognitive radio systems

Abstract: In this paper, we evaluate a novel contention-aware channel selection algorithm that focuses on energy efficiency improvement of a secondary network (SN) in a scenario where other non-cooperating SNs are also using the primary resources. We present a detailed energy efficiency analysis and we study how the time between two consecutive sensing periods affects the energy efficiency. Our analysis proves that a categorization of the idle channels based on their contention level and the selection of the less conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This scenario is applicable to wireless sensor networks in which child nodes can employ the channel switching strategy in order to improve their average capacity while fulfilling the minimum average capacity constraint of the parent node. Also, it can be stated that the channel switching strategy may improve the energy efficiency of the communication system by requiring a lower average power to achieve the same average channel capacity achieved by the conventional methods [32,33].…”
Section: System Model and Problem Formulationmentioning
confidence: 99%
“…This scenario is applicable to wireless sensor networks in which child nodes can employ the channel switching strategy in order to improve their average capacity while fulfilling the minimum average capacity constraint of the parent node. Also, it can be stated that the channel switching strategy may improve the energy efficiency of the communication system by requiring a lower average power to achieve the same average channel capacity achieved by the conventional methods [32,33].…”
Section: System Model and Problem Formulationmentioning
confidence: 99%
“…Zhao and others tackled the problem of interference estimation in a channel, in a scenario with one primary user and multiple secondary users [13]. Mesodiakaki and others evaluated a novel, contention-aware channel selection algorithm that focused on energy efficiency improvement in a secondary network, in a scenario where other, non-cooperating secondary networks were also using the primary resources [14]. Mesodiakaki and others evaluated the performance of a secondary network coexistence scheme, in terms of fairness, and showed that, in comparison to other state-of-the-art approaches, it could achieve throughput and energy efficiency gains, while maintaining fairness among the coexisting secondary networks [15].…”
Section: Related Workmentioning
confidence: 99%
“…By re-defining P idle as P(A 0 |A 0 ), throughput was acquired, as shown in (13): To calculate an effective throughput, time slot utilization, U ts , was defined as the ratio of a successful transmission period over the total time period, as shown in (14) below:…”
Section: Bayrakdarmentioning
confidence: 99%
“…Spectrum sensing in multi-channel systems spends a significant portion of time and energy resources due to the large number of sensed channels [4]. Thus, many works in the literature have investigated this problem, where some energyefficient CSS schemes have been proposed.…”
Section: Introductionmentioning
confidence: 99%